The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.29302/oeconomica.2014.16.1.25
|View full text |Cite
|
Sign up to set email alerts
|

"The Linkage Between Intangibles And Profitability "

Abstract: The intangibles can be viewed as strategic assets, since their inclusion in the structure of the total assets allows economic entities to extract a "competiveness rent" and, thus, to enhance the outcomes of their activity. This paper seeks to provide some empirical evidences for the effects exercised by shocks emerged at the level of intangible-to-total assets ratio on profitability in the case of 562 large companies listed on Frankfurt Stock Exchange and London Stock Exchange. We found that, for the full samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…This evidence does not correspond to the ones obtained by Omil et al (2011), who verified that high-profitable firms are strongly focused on managing their intangibles, which leads to a greater impact and increase on return on assets. In fact, for the estimation of this indicator of performance, intangibles appear to be irrelevant or negatively associated, which contradicts the positive impact found by Bedi (2019), , Nadeem et al (2016), Pucci et al (2015), Tudor et al (2014) and Pal and Soriya (2012).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This evidence does not correspond to the ones obtained by Omil et al (2011), who verified that high-profitable firms are strongly focused on managing their intangibles, which leads to a greater impact and increase on return on assets. In fact, for the estimation of this indicator of performance, intangibles appear to be irrelevant or negatively associated, which contradicts the positive impact found by Bedi (2019), , Nadeem et al (2016), Pucci et al (2015), Tudor et al (2014) and Pal and Soriya (2012).…”
Section: Discussionmentioning
confidence: 72%
“…The negative or null impact of other intangible assets on TURN is not the most accepted premise in the literature. In fact, these results are not consistent with the commonly positive effect of intangibles on performance, in particular on turnover (Fontana et al, 2018;Osinski et al, 2017;Shakina and Molodchik, 2014;Tudor et al, 2014;Tanfous, 2013;Omil et al, 2011;Heiens et al, 2007), although corroborating the findings of Pucci et al (2015) who found no positive impact of IC measured by intangible assets on turnover.…”
Section: Pearson Correlationsmentioning
confidence: 72%
See 2 more Smart Citations